Effect of glucoraphanin from broccoli seeds on lipid levels and gut microbiota in high-fat diet-fed mice. (May 2020) - Xu, Xinxing; Dai, Mei; Lao, Fei; Chen, Fang; Hu, Xiaosong; Liu, Yuping; Wu, Jihong
Graphical abstract: Highlights: Glucoraphanin showed the highest bioaccessibility after in vitro gastrointestinal digestion. Glucoraphanin modulated lipid profiles and metabolism related gene expression. Glucoraphanin supplementation changed the composition and richness of gut microbiota. Correlation analysis between biochemical factors and gut microbes was investigated. Abstract: Glucoraphanin was found to be the most abundant glucosinolate both in crude broccoli and after in vitro gastrointestinal digestion, with a bioaccessibility of 46.2 ± 0.4%. Glucoraphanin has been reported as a stable precursor of the nuclear factor (erythroid-derived 2)-like 2 (Nrf2) inducer sulforaphane which correlated with obesity. Thus, the effects of glucoraphanin on lipid metabolism and gut microflora in high-fat diet-fed mice were investigated. Glucoraphanin decreased liver weights and adipose tissue masses, concentrations of serum inflammatory factors, and the expression of genes of FAS and increased the expression of genes of PPARα, CPT1, ACOX in the liver. Glucoraphanin also decreased the Firmicutes / Bacteroidetes ratio and the abundance of microbes positively correlated with the high-fat diet in intestinal microbiota. The findings illustrate that glucoraphanin is a potential anti-obesity potential substance and suggest the utilization of seed flours and bio-products of glucoraphanin-rich cruciferous vegetables in nutraceuticals and functional foods.